Napoleon, symbol for an age : A brief history with documents - Blaufarb, Rafe. (Bedford series in history and culture, 2008)
In this collection of wide-ranging primary sources - including confidential memoranda and correspondence, speeches, memoirs, letters, police reports, and songs, most of which appear in English translation for the first time - Rafe Blaufarb situates Napoleon within his time while opening a broad perspective on the nature and impact of Napoleonic rule.